Holomorphic Riemannian Maps - Şahin, B. (Журнал математической физики, анализа, геометрии, 2014)
We introduce holomorphic Riemannian maps between almost Hermitian manifolds as a generalization of holomorphic submanifolds and holomorphic submersions, give examples and obtain a geometric characterization of harmonic holomorphic Riemannian maps from almost Hermitian manifolds to Kähler manifolds. Введены голоморфные римановы отображения между почти эрмитовыми многообразиями как обобщение голоморфных подмногообразий и голоморфных субмерсий, приведены примеры и получена геометрическая характеристика гармонических голоморфных римановых отображений почти эрмитовых многообразий на кэлеровы многообразия.